THE IMPLEMENTATION OF ACCREDITATION SCORING CALCULATIONS IN ALL WEB-BASED ACCREDITATION AGENCIES - Andie Andie; Hasanuddin Hasanuddin (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
Accreditation is an assessment activity to determine the eligibility of a department and higher education. Accreditation aims to determine the eligibility of departments and universities based on criteria that refer to the national higher education standards and guarantee the quality of departments and universities externally in both academic and non-academic fields to protect the interests of students and the community. All accreditation agencies have different accreditation instruments. The scoring calculation can be done automatically through the application of the respective accreditation agency and can only be seen by the assessment team, while departments and universities cannot see it. so far, universities and departments can only calculate accreditation scores manually using the excell application based on accreditation assessment instruments and matrices. Therefore, the research team wants to create a web-based application that can calculate accreditation scores independently to calculate accreditation assessment scores quickly and accurately.